In-vitro Evaluation of Fungicide Sensitivity of Tomato Leaf Blight Pathogens - Ogolla, Fredrick; Nyakinywa, Ruth; Chabari , Samson; Onyango, Benson (Talenta Publisher, 2021)
Tomato early and late blight diseases caused by Alternaria solani and Phytophthora infestans respectively, are constraints to tomato production globally. Conventional use of commercial synthetic fungicides in management of tomato blight disease has become a key input for tomato production among farmers in Tharaka Nithi County, Kenya. Indiscriminate use and application of sub-lethal doses of fungicides negate disease management efforts, and may lead to gradual fungicide resistance. Yet, local tomato farmers have continued to use the fungicides without periodic evaluation of their effectiveness. This study was carried out in-vitro to evaluate the efficacy of six synthetic commercial fungicides used by farmers around River Ruguti, against two tomato leaf blight pathogens; Alternaria solani and Phytophthora infestans. The poison food method was used to evaluate fungicides known by trade names and application levels; Mancozeb (640 g kg-1) + Metalaxyl (40 g kg-1), Mancozeb 640 g/kg + Metalaxyl 80 g/kg, Mancozeb, Propineb700 g/kg + Cymoxanil 60 g/kg, Carbendazim and Triticonazole at different concentration (25%, 50% and 75%). The in-vitro plate experiment was laid out in a Complete Randomized Design with 3 replicates, and data on mycelia growth inhibition analyzed through General Linear Model (α=.05) and significant means separated using Least significant difference (LSD) using Scientific Analysis System version 9.4. All the tested fungicides significantly (p≤ 0.05) inhibited mycelial growth of tested pathogen. Percentage inhibition for early blight pathogen (Alternaria solani) was 80.42% compared to late blight pathogen Phytophthora infestans at 69.51%. Mancozeb (640 g kg-1) + Metalaxyl (40 g kg-1) and Propineb700 g/kg + Cymoxanil 60 g/kg recorded higher per cent inhibition of mycelia growth of 92.4% and 89.71% respectively. Carbendazim recorded lower per cent inhibition of 39.15%. Mycelia growth inhibition increased with an increase in fungicide concentration. Lower inhibition of 71.78% was observed at 25% concentration as compared to 50% and 75% with 76.77% and 76.36% respectively. Fungicides screened varied in mycelia inhibition against P. infestans and A. solani isolates with Mancozeb (640 g kg-1) + Metalaxyl (40 g kg-1) and Propineb700g/kg +Cymoxanil 60g/kg giving significantly (p≤ 0.05) better inhibition while Carbendazim had the lowest inhibition effect. Increased fungicide concentration effectively inhibited mycelia growth. Thus higher concentration of fungicide application is recommended in cases where there is low efficacy of fungicides.